Formulasi dan Uji Aktivitas Sediaan Emulgel Ekstrak Daun Talas (Colocasia esculenta (L). Schott) terhadap Bakteri Staphylococcus aureus, Proteus mirabilis, Escherichia coli dan Pseudomonas aeruginosa - Ameliya, Helvi; Rustiani, Erni; Sulistiyono, Fitria Dewi (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Taro leaf (Colocasia esculenta (L). Schott) are known to contain flavonoid compounds that have antibacterial activity that causes wound infections. One of the topical dosage forms for the treatment of bacterial infections in wounds is emulgel which can convey the active substance of the drug with hydrophobic properties. Appropriate and effective topical administration is expected to reduce and prevent wound infection. This study aims to determine the antibacterial activity of taro leaf extract emulgel preparations against Staphylococcus aureus, Proteus mirabilis, Escherichia coli and Pseudomonas aeruginosa bacteria based on the width of inhibition (LDH) value. Methods: Taro leaf extract emulgel preparations were made as many as 4 formulas with different extract concentrations namely (F1) 5%, (F2) 7.5% and (F3) 10% and (F0) as a negative control containing only emulgel base. Testing of emulgel preparations includes organoleptic, homogeneity, pH, spreadability, and viscosity. Antibacterial testing using disc paper diffusion method with positive control sulfadiazine silver and negative control emulgel base. Results: The results showed that the emulgel preparation was viscous, brownish green in color, and had a distinctive smell of taro leaf extract. The mean pH values were 5.657-5.912, spreadability 5.845-6.258 cm, and viscosity 7830-9780 cps. Statistical test results of antibacterial activity of taro leaf extract emulgel with sig 0.000 <0.05 showed that all concentrations of taro leaf extract emulgel provide inhibition against bacteria. Conclusion: The best antibacterial activity was shown by 10% concentration of taro leaf extract emulgel against Staphylococcus aureus (10.69mm), Pseudomonas aeruginosa (10.50mm), Escherichia coli (10.34mm) and Proteus mirabilis (10.14mm) all with strong inhibition zone category (10-20mm).